APPLICATION OF NANOCRYSTALS IN TREATMENT OF CHRONIC APICAL PERIODONTITIS - Kostyrenko О.P.; Melnyk, V.L.; Shevchenko, V.K.; Sylenko, Yu.I.; Yeroshenko, G.A. (World of Medicine and Biology, 2020)
The use of nanocrystals for the treatment of chronic apical periodontitis is the current level of nanomedicine. We examined and treated 11 patients aged 17 to 67 years for aggravated and chronic apical periodontitis using the author’s method of using phosphate buffer. An assessment of clinical and radiological data was carried out, which confirmed the process of restoration of periapical tissues in 11 patients. She showed that the regeneration of the apical and adjacent areas of the periodontal in 10 cases had a positive trend already after 29-30 days from the start of treatment; in 1 case, there was a slowed down dynamics of recovery after 40 days from the start of treatment due to the presence of somatic pathology in the patient. The proposed method for the treatment of chronic apical periodontitis on the basis of the obtained treatment results requires further study in the long term with the aim of widespread implementation in practical dentistry.